'Infernal Cycle': Why War and Peace Repeat Themselves in Libya - Polat, Furkan (Routledge Journals, Taylor & Francis Ltd, 2025)
After the fall of the Gaddafi regime, Libya has experienced recurring periods of war and peace. War between armed groups in 2014 and 2019 gave way to periods of relative stability in which peace talks were on the table. This study addresses the question of why there is a cycle between periods of war and peace in Libya. Contrary to the arguments of the war legacy, anarchy, bad governance and the nature of peace agreements in the existing literature, it examines the cycle of war and peace in this specific case through the logic of classical balance of power theory, focusing on the power struggle between actors. In this context, the study argues that shifts in the balance of power between armed groups lead to war, while the reestablishment of the balance leads to peace.
Keywords: Balance of power; recurrence of war; negative peace; Libya